BUILDING COST-EFFECTIVE CLOUD DATA WAREHOUSES: A STRATEGIC APPROACH - Lakshmi Ayyappan, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the strategic approach to building cost-effective cloud data warehouses, examining various aspects from business requirements analysis to environmental responsibility. It investigates how organizations can optimize their data warehouse implementations through managed services, security measures, and sustainable practices. The article synthesizes findings from multiple studies to demonstrate the transformative impact of cloud-based solutions on operational efficiency, cost reduction, and environmental sustainability. The article presents comprehensive analyses of implementation best practices, security frameworks, and cost optimization strategies, providing organizations with actionable insights for successful cloud data warehouse deployments. Through articles of real-world case studies and industry research, this work highlights the importance of thorough planning, continuous optimization, and adherence to best practices in achieving successful cloud data warehouse implementations.